Fairness in coffee value chains: organizational solutions for the self-governance of small producers - Fantini, Andrea; Samoggia, Antonella; Bonfigli, Leonardo; Quiñones-Ruiz, Xiomara F. (Frontiers in Sustainable Food Systems, 2025)
IntroductionThis research aims to identify key organizational mechanisms that enable small coffee producer associations to create equitable and sustainable alternatives to conventional supply chains, which are characterized by strong inequities and asymmetries. Through an in-depth case study of northern Colombia, this study reveals how collective organization and equitable decision-making processes can transform power dynamics, allowing small-scale producers to retain greater value and establish economic, social, and environmental sustainability.MethodsBuilding on a comprehensive theoretical framework of fairness—encompassing distributive, procedural, interactional, and environmental dimensions—the research employs a mixed-methods approach combining quantitative data from 40 coffee producers regarding their perceptions of fairness with qualitative insights from semi-structured interviews with producers and technicians cooperating within the case study.ResultsThe central finding demonstrates that producer-led collective governance structures directly strengthen self-determination and enable small-scale farmers to challenge dominant supply chain inequities. Specifically, the study reveals that equitable decision-making processes are the critical mechanism through which coffee associations successfully retain value and achieve sustainability across multiple dimensions.DiscussionThis research makes an original contribution by empirically demonstrating how producer associations can serve as viable organizational models for transforming global agricultural value chains. By empirically demonstrating that grassroots collective action provides a robust alternative to conventional approaches to supply chain sustainability, the study offers concrete evidence of the potential for small-scale producers to effect meaningful change in the coffee industry.